The Role of Pesantren in Realizing the Quality of Students' Self Through Guidance and Counseling - Ummah Karimah; Usman Al Farisi; Sadari Sadari (Future Science, 2023)
This research aims to determine the role of guidance and counseling in Islamic Boarding Schools to improve the self-quality of students who contribute to sustainable development. This study used a descriptive qualitative method. The primary data source for this research is teachers at the Yapink Tambun Bekasi Islamic Boarding School. Meanwhile, for secondary data, researchers used books and journals related to guidance and counseling in Islamic boarding schools and the personal qualities of students. Data collection techniques use interview and observation methods. data analysis techniques use data reduction, data presentation, and conclusion. The findings show that many Islamic boarding schools implement various programs to realize the self-quality of students, such as students who can become part of an institution that focuses on the community's economy so that they can contribute to the economic development of people who have self-quality so that they can realize sustainable development programs. One of them is providing Santri training through the guidance and counseling program at Islamic Boarding Schools. The challenges in realizing the quality of Santri are the unavailability of guidance and counseling teachers in Islamic Boarding Schools, there is still no special program to realize the quality of Santri and policy makers do not yet understand the implementation of the guidance and counseling program for Santri. The solution is that Islamic Boarding School policy makers understand the urgency of guidance and counseling in Islamic Boarding Schools to help students' problems. This research implies that Islamic boarding school policy makers design Islamic Boarding School programs through guidance and counseling according to the student's abilities to realize the students' self-quality. Research findings can contribute to understanding and knowledge to islamic boarding schools in understanding the importance of guidance and counseling in Islamic Boarding Schools.